Cloud-To-Ground Lightning Flashes Under The Influence Of Pollution In Malaysia And Some Countries - Zikri Abadi, Baharudin; Ahmad Idil, Abdul Rahman; M., Zainol; Mohamad Rom, Tamjis; Mohd Ariff, Mat Hanafiah; Mohd Ruddin, Ab Ghani; Lokman, Abdullah; Othman, Aman; Hassan, Adnan; Ahmad Aizan, Zulkefle; Ismail, Abu Shah; P. N. S. A. B., Rahman; et al. (Asian Research Publishing Network (ARPN), 2016)
The effect of air pollution produced from world war, industrial activities and transportation clearly can change the earth ecology system such as the atmospheric conditions. Base on few studies reported from by researcher in USA, Brazil, Spain and South Korea researcher have proven that the pollution effect can enhance the activity of lightning. Those information above motivate Advanced Multidisciplinary System Technology researcher in UTeM to report the cloud-to-ground lightning flashes in Malaysia the influence of pollution. Particulate Matter (PM10) and Sulfur Dioxide (SO2) concentration were used as gross indicator of Cloud Condensation Nuclei (CCN) and examined in relation to the urban increase in CG lightning activity. PM10 concentration recorded in Subang, Ipoh and Bayan Lepas were 51, 50 and 49μgm/m³ respectively. Meanwhile, SO2 concentration recorded were 8, 7.9, 7.7μgm/m³. The three urban areas have average number of CG lightning flashes of 200, 197 and 184. An analysis related number of CG flashes against pollutants show positive correlation in Malaysia with reading of 0.94. This indicates PM10 and SO2 concentration have high influential factor in enhancement of CG lightning activity in Malaysia.